تحليل تطور مؤشرات بيئة أداء الأعمال في الجزائر - بكطاش، فتيحة; بوعزارة، أحلام (جامعة عبدالحميد بن باديس مستغانم - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2020)
يهدف هذا البحث الى تسليط الضوء على وضعية مناخ الأعمال الجزائري، ومكانة تنافسية اقتصاده مقارنة مع مجموعة من الدول العربية وفقا لتحليل مختلف المؤشرات الصادرة عن بعض الهيئات والمنظمات الدولية في تصنيفها للدول كمؤشر الحرية الاقتصادية، مؤشر التنافسية العالي، مؤشر ممارسة أنشطة الأعمال ومؤشر مدركات الفساد. وتوصل البحث إلى مجموعة من النتائج أهمها أن الجزائر يسودها مناخ استثماري غير تنافسي مقارنة مع دول عربية ومجاورة لها لا تقل أهمية ومكانة عنها راجع لكثرة تدخل الدولة في النشاط الاقتصادي وعدم جاهزيته للمنافسة الدولية، ما يحتاج إلى الكثير من الاصلاحات أهمها محاربة الفساد المتفشي خاصة في القطاعات الحساسة.
This research aims to highlight the situation of the Algerian business climate, and the competitive position of its economy compared to a group of Arab countries according to the analysis of the various indicators issued by some international organizations in their classification of countries as an indicator of economic freedom, such as Global Competitiveness Index, Doing Business Index and Corruption Perceptions Index. The research reached a set of results, the most important of them that Algeria is dominated by a non-competitive investment climate, compared to neighboring and Arab countries that are no less important and prestigious than they are, this is due to the large number of state interference in economic activity and its lack of preparedness for international competition, that needs a lot of reforms, the most important of which is the fight against corruption, especially in sensitive sectors.
Keywords: الأنشطة الاقتصادية -- التنمية الاقتصادية -- الجزائر